Multisensory Interactive Digital Text for English Phonics Instruction with Bilingual Beginning Readers - Beth A. O'Brien; Reneé Seward; Dongbo Zhang (MDPI AG, 2022)
We investigated a technology-based tool for teaching English letter-sound correspondences with bilingual children learning phonologically and typologically distant languages: English and Chinese. We expect that learning about print at the phoneme level may be particularly challenging, given children's experience with the morphosyllabic language of Chinese. This randomized-controlled study with 90 kindergarteners examined the effects of an iPad-based supplementary reading program compared with a control condition. The See Word Reading® program utilized picture-embedded cues for teaching phonics within lessons directed at the letter, word, and text levels. Measures of decoding, word reading, and spelling were taken at the pretest, posttest, and follow-up for both groups. Results showed better gains in word reading for the reading group, indicating the positive impact of this supplementary reading tool. Further, data collected online from the app showed that different types of letter-sound pairings were more challenging to learn, including pairings that are inconsistent and with phonemes that are specific to English.